Adaptations in athletic performance and muscle architecture are not meaningfully conditioned by training free-weight versus machine-based exercises: Challenging a traditional assumption using the velocity-based method - Hernández-Belmonte, A.; Buendía-Romero, Á.; Franco-López, F.; Martínez-Cava, A.; Pallarés, J. G. (Scandinavian Journal of Medicine & Science in Sports, 2023)
Background Although the superior effectiveness of free-weight over machine-based training has been a traditionally widespread assumption, longitudinal studies comparing these training modalities were scarce and heterogeneous.